MINERAL MIXTURE SUPPLEMENTATION FOLLOWED BY TIMED AI PROTOCOL FOR IMPROVING FERTILITY STATUS OF POSTPARTUM DAIRY CATTLE - VELLADURAI, C; NAPOLEAN, R E; SELVARAJU, M (The Indian Journal of Animal Reproduction, 2016)
MINERAL MIXTURE SUPPLEMENTATION FOLLOWED BY TIMED AI PROTOCOL FOR IMPROVING FERTILITY STATUS OF POSTPARTUM DAIRY CATTLE.